A Rare Case of Clival Hemangioma Simulating Chordoma - Isolan, Gustavo Rassier; Smith, Alessandra Locatelli; Meotti, Camila; Telles, João Paulo Mota; Rabelo, Nícollas Nunes; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2024)
Primary intraosseous hemangiomas are rare, benign, vascular malformations that account for ∼1% of all primary bone neoplasias. A 59-year-old female patient with unknown comorbidities had a history of headache, visual impairment and dizziness that led to the diagnosis of a clivus tumor. Two resections were attempted through transcranial and transnasal transsphenoidal approach in the last two years in another hospital. The initial MRI scan showed an expansive lesion with T2 hyperintense signal and diffuse, heterogenic contrast enhancement. Clival chordoma was the main diagnostic hypothesis done. A CT scan was performed to evaluate the extent of clival invasion, the sinus anatomy, and the clival destruction - all simulating clival chordoma. The interdisciplinary tumor board decided to proceed with endoscopic endonasal tumor resection. There were no postoperative complications and the histopathological analysis revealed a primary intraosseous haemangioma. Skull base intraosseous hemangiomas are rare entities, with a limited number of case reports found after literature reviews, especially in the clival region. The clinical pattern and imaging characteristics can vary widely according to the tumor extension and development, simulating some other common tumors found at this topography. We present a case report of a clival intraosseous hemangioma presenting as an isolated abducens paresis with a positive outcome after intranasal endoscopic resection after two years of follow-up.
Keywords: chordoma; hemangioma; neurosurgery; tumor